Determinants and consequences of rural‐to‐urban migration patterns in China: Evidence from sequence analysis. Issue 2 (15th June 2021) - Chen, Zhenxiang; Lu, Yao; Treiman, Donald J.
Abstract: This paper adopts a life course perspective that captures the migration trajectory for rural‐to‐urban migrants in China during the observation window. By taking this trajectory approach, we aim to advance the understanding of divergent rural‐to‐urban migration patterns in China and their determinants and consequences. We use data from the Survey of Internal Migration and Health in China (IMHC) and focus on individuals' migration experience between age 14 and 40. First, we apply sequence analysis to characterise the main rural‐to‐urban migration patterns by different timing, duration, frequency, and direction and identify seven common patterns. We next examine the determinants of these patterns. The results suggest that demographic characteristics, socio‐economic background, and hometown characteristics shape migration trajectories in complex ways, highlighting that social origin can substantially determine migration patterns of rural Chinese. Furthermore, we examine via a counterfactual framework how the seven migration patterns shape migrants' occupational attainment while taking account of self‐selection into different migration trajectories. The findings show that (i) there is self‐selection into migration trajectories that has implications for occupational status and (ii) non‐transient adult urban migration is associated with higher occupational attainment whereas other types of migration are not.